Chromic(III) Sulfamate as a Versatile Catalyst for Organic Synthesis - Liu, Qing; Li, Zhen (Asian Journal of Chemistry, 2011)
Chromic sulfamate was synthesized and used as catalyst for the first time in various organic reactions such as the transformation of aldehydes or ketones and indole to bis(indolyl)methanes, the transformation of aldehydes and acetic anhydride to 1,1-diacetates and Biginelli reaction. The advantages of the chromic sulfamate are ease of preparation, easy handling, simple workup and versatility.